PENGARUH TEKNIK SELF CONTROL TERHADAP PERILAKU KECANDUAN INTERNET SISWA DI SMKN 1 PEKANBARU - Sri Noviarti Rusdi; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of self control techniques on internet addiction behavior of students of SMKN 1 Pekanbaru. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the scale of measurement of internet addiction behavior which consists of 50 items before the validity, and after the validity is obtained valid items number 31 items with validity of 0.381 and reliability of 0.888. And getting the subject of 7 students of SMKN 1 Pekanbaru who were identified as having high levels of internet addiction behavior. The data analysis technique used is non-parametric statistical technique using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. This is known from